2019
DOI: 10.1097/qad.0000000000002200
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes for lung cancer resection surgery in HIV infection

Abstract: Objective: Lung cancer is the leading cause of cancer death in people living with HIV (PWH). Surgical resection is a key component of potentially curative treatment regimens for early stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Data on the prognosis following surgery in PLWH with malignancy are limited. In a national cohort, short-term outcomes after surgical lung resection did not differ significantly between lung cancer patients with and without HIV well managed with ART medication [ 26 ]. Another study reported that HIV status did not adversely affect outcomes in African patients with head and neck cancer [ 27 ], but this conclusion was limited by the suboptimal medical treatment received by all participants in local areas.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prognosis following surgery in PLWH with malignancy are limited. In a national cohort, short-term outcomes after surgical lung resection did not differ significantly between lung cancer patients with and without HIV well managed with ART medication [ 26 ]. Another study reported that HIV status did not adversely affect outcomes in African patients with head and neck cancer [ 27 ], but this conclusion was limited by the suboptimal medical treatment received by all participants in local areas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating perioperative outcomes in patients undergoing colorectal, cardiac, and thoracic surgery in the United States demonstrated no differences in mortality. 3032 However, other studies demonstrated an increased risk of perioperative and 1-year mortality among patients with HIV, with CD4 count, HIV viral loads, and hypoalbuminemia as risk factors for complications. 15,33 Lin et al investigated the outcomes of open abdominal aortic surgery in 48 patients with HIV with aneurysms or aortoiliac occlusive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent data collection about a national cohort of LC patients showed that surgery is safe in HIV-positive patients (n = 137), being surgical complications and 30-day mortality similar to those uninfected ones (n = 8234) [47]. Small single institution series of NSCLC patients (n = 6) who underwent lobectomy or segmentectomy seems to confirm the feasibility of surgery in HIV-positive patients [48].…”
Section: Surgery and Radiotherapymentioning
confidence: 91%